Translation and transliteration of Islamic terms - Adel Muhi, Abeer (Opción, 2019)
This paper attempts to shed light on the problem of translation and transliteration of Islamic terms. It aims at discussing problems that face translators to accomplish their goals, and the strategies they use to overcome them. The purpose of this paper also is to investigate the efforts of translators in the field of translating and translit- erating of Islamic terminology. Moreover, the researcher summarizes the process and procedures of transforming the Islamic terms from the source language into target language.